Repair of Chronic Complete Traumatic Rupture of the Common Calcaneal Tendon in a Dog, Using a Fascia Lata Graft - Shani, J.; Shahar, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A 3-month-old male Cocker Spaniel was presented with the complaint of chronic right hind leg lameness. The owner described superficial trauma at the area of the hock, which was noticed immediately after delivery. History, habitus, physical examination, and radiography suggested rupture of the common calcaneal tendon. This report describes the successful repair of complete rupture of the common calcaneal tendon, with loss of tendon length, using a fascia lata free graft.The following case report describes the successful repair of a chronic complete traumatic rupture of all components of the Achilles tendon with loss of tendon length, in a 3-month-old puppy, using a tensor fascia lata free graft. Due to the young age of the animal no internal fixation was used to protect the graft, and external coaptation was used instead. Achilles tendon rupture is a relatively common injury in humans and many methods of repair are reported for acute and chronic ruptures. The medical and veterinary literature is reviewed with regard to the pathogenesis and treatment of Achilles tendon rupture.
Keywords: Achilles tendon; tensor fascia lata; graft